New energy crop alternatives for Northern Europe: Yield, chemical and physical properties of Giant knotweed (Fallopia sachalinensis var. 'Igniscum') and Virginia mallow (Sida hermaphrodita). (15th November 2021) - Papamatthaiakis, Nikolaos; Laine, Antti; Haapala, Antti; Ikonen, Risto; Kuittinen, Suvi; Pappinen, Ari; Kolström, Marja; Mola-Yudego, Blas
Highlights: Fallopia sachalinensis "Igniscum" & Sida hermaphrodita assessed as energy crops. Yields range 5.41–27.67 odt/ha, and 6.72–16.72 odt/ha, respectively. Results show good physical and chemical properties as feedstock for pellets. Commercial cultivation viable in climatic & soil conditions of Northern Europe. Abstract: New energy crops adapted to northern conditions of Europe can broaden the portfolio of agricultural based biofuel options in an area with currently few alternatives. This study evaluates two energy crops, giant knotweed ( Fallopia sachalinensis var. 'Igniscum') and Virginia mallow ( Sida hermaphrodita ), as possible biomass feedstocks for biofuels in southern Finland. The collected data includes yield productivity, physical and chemical properties, and energy content. The dry matter yield of giant knotweed ranges from 5.41 odt·ha −1 to 27.67 odt·ha −1, whereas Virginia mallow ranges from 6.72 odt·ha −1 to 16.72 odt·ha −1 . Pellets from both crops meet the requirements regarding standards. Giant knotweed presents a bulk density of 677.71 kg·m −3 and Virginia mallow 725.18 kg·m −3 . The results of mechanical durability of giant knotweed do not exceed the minimum threshold of the standards, with 96.73 w-%, while Virginia mallow is 92.86 w-%. The analysis of the ash content results in 1.5% for giant knotweed and 2.19% for Virginia mallow. The quantities of chlorine (Cl) and sulphur (S) are below the recommended thresholds. Finally, the energy content with moisture content of 5 w-% of giant knotweed and Virginia mallow were 19.97 MJ·kg −1 and 19.68 MJ·kg −1, respectively. Both crops prove are valid alternatives in the climatic and soil conditions of Northern Europe.